The Instant Gratification Trap: Managerial and Societal Challenges - Paché, Gilles (Advances in Social Sciences Research Journal, 2025)
The rise of ultra-fast delivery is fundamentally altering consumer habits, fostering a culture of immediacy where waiting has become an anomaly. This position paper examines the managerial and societal implications of the consumer’s relentless pursuit of instant gratification. By analyzing how speed reshapes consumer expectations, it demonstrates that the perceived value of goods and services is now determined not only by their quality or price but also by their immediate availability. The cult of speed is transforming decision-making processes, promoting impulsive behavior, and forcing companies to realign their supply chains to meet the demand for immediacy. Beyond business, this culture is influencing social interactions, even affecting how individuals approach human relationships. Far from being a trivial matter, this transformation presents significant challenges: reduced time for reflection, heightened logistical pressure on companies, and a disruption of social and environmental balances. By paving the way for critical reflection on the limits of the cult of speed, the author raises concerns about the troubling future of societies where time becomes a resource to be optimized at any cost.